2019
DOI: 10.3892/etm.2019.8142
|View full text |Cite
|
Sign up to set email alerts
|

A meta‑analysis of the safety and efficacy of bosentan therapy combined with prostacyclin analogues or phosphodiesterase type‑5 inhibitors for pulmonary arterial hypertension

Abstract: Bosentan is an effective drug for the treatment of pulmonary arterial hypertension (PAH). The aim of the present meta-analysis was to examine the evidence concerning the efficacy and safety of bosentan therapy combined with prostacyclin analogues or phosphodiesterase type 5 (PDE-5) inhibitors for treating PAH. Eligible published studies were collected from Embase, PubMed, The Cochrane Library and the website. Heterogeneity was assessed using the Cochran Q-statistic test. Results were presented as risk ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The results of previous meta-analysis showed that sildenafil combined with bosentan for PAH was effective in reducing mPAP, increasing 6MWD, reducing Borg dyspnea score, and improving WHO functional class, which is consistent with the results of this study. [48] However, when selecting the combination of bosentan and sildenafil, the drug-drug interactions should also be considered. Studies have shown that prolonged co-administration of bosentan and sildenafil results in lower plasma concentrations of sildenafil, and that the combination of sildenafil with P450 isoenzyme inducers such as bosentan results in increased clearance and a weaker therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous meta-analysis showed that sildenafil combined with bosentan for PAH was effective in reducing mPAP, increasing 6MWD, reducing Borg dyspnea score, and improving WHO functional class, which is consistent with the results of this study. [48] However, when selecting the combination of bosentan and sildenafil, the drug-drug interactions should also be considered. Studies have shown that prolonged co-administration of bosentan and sildenafil results in lower plasma concentrations of sildenafil, and that the combination of sildenafil with P450 isoenzyme inducers such as bosentan results in increased clearance and a weaker therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The conservative management focuses on monotherapy including endothelin receptor antagonists, phosphodiesterase-5 inhibitors, and prostanoids. In a meta-analysis of eight studies, it was shown that bosentan and phosphodiesterase-5 inhibitors improved exercise tolerance and reduced vascular remodeling in patients, at the cost of a few adverse effects [16].…”
Section: Discussionmentioning
confidence: 99%